Optical magnetic multimodality imaging of plectin-1-targeted imaging agent for the precise detection of orthotopic pancreatic ductal adenocarcinoma in mice - Zhang, Wenjia; Liang, Xiaolong; Zhu, Liang; Zhang, Xinyu; Jin, Zhengyu; Du, Yang; Tian, Jie; Xue, Huadan (EBioMedicine, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal malignancy worldwide, and the precise detection is challenging currently. Magnetic particle imaging (MPI) is suitable for imaging deep and internal PDAC tumours because of its high sensitivity and unlimited imaging depth. The purpose of this study was to utilize the MPI, in combination with fluorescence molecular imaging (FMI) and magnetic resonance imaging (MRI), to advance the in vivo precise detection of PDAC xenografts. The PDAC targeted plectin-1 peptide and IRDye800CW were conjugated to the superparamagnetic iron oxide nanoparticles (PTP-Fe3O4-IRDye800CW) for the PDAC-targeting triple-modality imaging. Subcutaneous and orthotopic PDAC mouse models were established. FMI, MPI, and MRI were performed for dynamic and quantitative observation of PDAC tumours. Histological staining analyses were used for ex vivo validation. PTP-Fe3O4-IRDye800CW nanoparticles possessed great triple-modality imaging performance and specific targeting to plectin-1 expressed on PDAC cells. For in vivo multi-modality imaging of orthotopic PDAC models, the PTP-Fe3O4-IRDye800CW nanoparticles demonstrated higher specificity, even distribution, and longer retention effects in tumours for over 7 d compared with Con-Fe3O4-IRDye800CW nanoparticles. (MPI, 2d post-injection: PTP-Fe3O4-IRDye800CW: 85.72% ± 1.53% vs. Con-Fe3O4-IRDye800CW: 74.41% ± 1.91%, **P < 0.01 (Student's t test)). Ex vivo histological and Prussian blue stainings were performed to validate the distribution of probes. These data demonstrate the feasibility of utilizing MPI for in vivo PDAC imaging and complement with FMI/MRI for a precise and comprehensive in vivo characterization of PDAC. This may benefit PDAC patients for precise diagnosis and guidance of therapy. This study was funded by the National Natural Science Foundation of China (Grant No. 62027901, 82071896, 81871422, 81871514, 81227901), Ministry of Science and Technology of China under Grant No. 2017YFA0205200, 2017YFA0700401, Beijing Natural Science Foundation (Grant No. 7212207), Elite Program of Dong Cheng District of Beijing (2020-dchrcpyzz-28), and Peking University Third Hospital (BYSYZD2019018, and jyzc2018-02).